Determination of Sensitive Frequency Bands for Cytotoxicity Analysis Using Microwave Dielectric Measurements - ATEŞ, Taha Fatih; ÖZKAN, Ali Osman (International Journal of Applied Methods in Electronics and Computers, 2025)
This study presents a comprehensive frequency-resolution analysis framework to identify biologically significant frequency bands for cancer cell monitoring in the 10–20 GHz range. By integrating statistical significance, effect size, dielectric deviation magnitude, and temporal stability analysis, the spectral response of cell cultures exposed to cytotoxic agents was systematically evaluated. The results revealed a dual-optimization environment: the 13.9–14.2 GHz range showed a statistically significant global maximum for signal coherence, while higher frequencies demonstrated superior dielectric contrast due to γ-dispersion mechanisms. To resolve this balance, a composite sensitivity score and band-averaged analysis were used. The evaluation identified the 16–18 GHz band as the optimum working region, offering significantly enhanced physical contrast and temporal robustness while maintaining a composite score almost identical to the statistical peak (<0.7% difference). This study demonstrates that data-driven, multi-criteria frequency selection provides a robust foundation for sensor design and paves the way for the development of highly sensitive, frequency-selective microwave biosensors for toxicological screening.